The usefulness, ease of use and trust toward uses of e-government services among the degree students in UiTM Kedah / Nur Inayah Ahmad Zaki and Nurnadia Salmi Zainall Abidin - Ahmad Zaki, Nur Inayah; Zainall Abidin, Nurnadia Salmi (2014)
This research study was carried out to explore the usefulness, ease of use and trust of e-government services among the degree students in UiTM Kedah. Researchers had examined three factors that influence the students to use e-government services. Factors included usefulness, ease of use and trust. This study was a descriptive research study. Quantitative data collection method and convenience sampling method had been used. The target population is the degree students in UiTM Kedah. This study used primary data collection method and secondary data collection method. Journal, internet research and text book had been used as secondary data collection. Questionnaire-based survey was used and 270 sets of questionnaires were distributed to respondents, however only 250 of the questionnaire being returned and the data will be analysed by using SPSS. Descriptive analysis, reliability test, Pearson correlation coefficient test and multiple regression analysis were being chosen as data analysis techniques. The questions and scales in questionnaires were considered to be reliable and all the hypothesis proposed in this research were accepted.